Factors affecting the evacuation decisions of coastal households during Cyclone Aila in Bangladesh. (2nd January 2016) - Ahsan, Md. Nasif; Takeuchi, Kuniyoshi; Vink, Karina; Warner, Jeroen
ABSTRACT: Despite sincere efforts by concerned agencies and recent improvements in hazard warnings, thousands of at-risk people did not evacuate during Aila, a category-I tropical cyclone that struck southwestern coastal Bangladesh in 2009. This study investigated the responses of the people affected by Aila to cyclone warnings and associated evacuation orders, and unveiled behavioural aspects that explain why they did or did not comply with the evacuation orders. Utilising the primary data collected from 420 households living in the severely affected coastal sub-district Koyra, located in Khulna District, this study found that although more than 97% of the households had received cyclone warnings and evacuation orders before Aila's landfall, only around 26% had evacuated. We also examined this study's empirical findings for factors that had dissuaded people from complying with the evacuation orders. Relevant test statistics along with results from principal component analysis suggested that the significant and systematic absenteeism of households from disaster preparedness training appears to be one of the key determinants that affected their evacuation decisions, along with factors related to warning messages, the attributes of cyclone shelters, risk perception, and socioeconomic aspects. A number of recommendations are also presented in this study for people at risk to improve their evacuation rates in future emergencies, not only to save their own lives but also to save their livestock.